ANALISIS DAN PERANCANGAN CLUSTERING SISWA BARU MENGGUNAKAN METODE K-MEANS PADA SMK NEGERI 1 KOTA JAMBI - Tandy, Juliana; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2019)
Every year there will be students who continue education to the next stage, including at SMK Negeri 1Kota Jambi, Event admission of new students is done every 1 year, in the selection process and receptionrequires the application of more efficient is to use the application, change the system Manual into thesystem computerized and perform a new grouping students by majors at SMK Negeri 1 Kota Jambinamely Computer Engineering and Networks, Accounting, Office Administration and Marketing.Therefore Final report with the title